Experimental study on horizontal-well multi-thermal fluid stimulation process in offshore heavy oil reservoirs - Yigang Liu; Jian Zou; Xianghai Meng; Fayuan Zhou; Hao Liu; Qiuxia Wang; Zhilin Qi; Jie Fan (Journal of Petroleum Exploration and Production Technology, 2020)
Abstract The development of offshore heavy oil is sensitive and complex, which is limited by factors such as platform space, economy, pollution and security, so conventional thermal recovery techniques such as cyclic steam stimulation and steam flooding have difficulty in achieving favorable development effect for offshore heavy oil reservoirs. Horizontal-well multi-thermal fluid stimulation (HW-MTFS) process is a relatively new thermal recovery technique, which combines the multiple advantages of gas injection, horizontal well and thermal recovery process. In this paper, the HW-MTFS physical model was firstly designed. Thereafter, the influences of different factors on steam absorption along horizontal wellbore were studied by sand-packed model experiments. Finally, the development performance of horizontal-well cyclic steam stimulation (HW-CSS) process and horizontal-well multi-thermal fluid stimulation process was compared by two groups of physical experiments. The results indicate that different injection factors significantly influenced the steam absorption along horizontal wellbore. Compared with steam injection, the multi-thermal fluid injection could effectively improve the steam absorption along horizontal wellbore. The HW-MTFS process had a higher oil rate and production, and the recovery of HW-MTFS process was 42% higher than that of HW-CSS in three cycles.